Analisis Pemilihan Media Promosi UMKM untuk Meningkatkan Volume Penjualan Menggunakan Metode Analytical Hierarchy Process (AHP) - Subiyantoro, Edi; Muslikh, Ahmad Rofiqul; Andarwati, Mardiana; Swalaganata, Galandaru; Pamuji, Fandi Yulian (Jurnal Teknologi dan Manajemen Informatika, 2022)
The increase in the number of creative industry entrepreneurs on the scale of UMKMs in Indonesia must be supported by several factors so that these businesses can develop. These factors range from business conditions, environment, facilities, and infrastructure, to technology. In terms of the use of technology, UMKM business actors can use it in various fields including the procurement of raw materials, the production process to the marketing and promotion stages of the products produced. This analysis aims to determine the weight the importance of the criteria to create an element of UMKM sales volume. In addition, it also helps UMKM actors in making decisions in choosing and using which alternative best suits their needs. Based on the results of the analysis of this study, it can be concluded that alternative social media is a priority criterion in increasing the sales volume of UMKM actors. Based on the overall average weight value, the alternative for social media is to expand the market by increasing the intensity of promotions with various social media. Such as WhatsApp Business, Instagram, Facebook, YouTube, and others to increase product sales for UMKM actors.